Virological diagnosis of Ebolavirus infection. Issue 5 (August 2015) - Smith, D. W.; Rawlinson, W. D.; Kok, J.; Dwyer, D. E.; Catton, M.
Abstract : Summary: Ebolaviruses, and the other viral causes of haemorrhagic fevers (VHF) have always posed special problems for diagnostic laboratories. These arise from the rarity of human infections, minimal documented experience with test delivery and interpretation, the paucity of established commercial or in-house assays, the lack of clinical material for test development and validation, the high level containment required for handling live virus, the ongoing evolution of the viruses, and the high personal and public health requirements for accurate diagnosis. This article addresses the current situation and the ongoing challenges associated with delivering timely, high quality and safe testing within Australia for people exposed as part of the current major outbreak of Ebolavirus disease (EVD) in Western Africa. The members of the Public Health Laboratory Network have developed deliverable and reliable nucleic acid detection tests, and also have the laboratory capacity to handle the live viruses if necessary. However delivering and maintaining these services necessitates high levels of experience in developing and applying tests for exotic and emerging infections, strong national and international links and collaborations, ongoing monitoring and reassessment of test design and performance, innovative approaches to generation of positive control material, and a regular quality assurance program.